Crecimiento económico en el servicio de televentas de la tienda comercial Baratodo, de la ciudad de Babahoyo. - Briones Acosta, Juan Alexis (2018)
The Comercial Baratodo store is a business unit belonging to the Unicomer Group focused on the marketing of furniture and appliances to the low to low middle sector, among its competitive advantages are the Telemarketing Service that the company offers in order to increase its participation in the market. In general terms, the telesales service of this company gives its client portfolio the convenience of acquiring an item from the comfort of its home by outsourcing its commercial management services, which has allowed the company to obtain a favorable economic growth. .